CRITERIA OF THE FORMATION OF THE MOST CONVENIENT LOAD-BEARING STRUCTURE IN THE BASIC LOAD STATE: TENSION AND BENDING - Marek FLIGIEL (Scientific Journal of Silesian University of Technology. Series Transport)
In this study, the criteria of an optimal formation of the most convenient load-bearing structure for the case of simple tension and bending are considered. As the criteria quantities, the following are accepted: the minimum value of the potential energy of deformation and a possibly equal relative volumetric value of the potential energy of deformation in the entire volume of a structural element and the activity duration of the internal forces of the load-bearing structure. The integral of the function of absolute stresses, which is determined for the constant volume of the structure, was accepted as a quantitative criterion of the activity duration of the internal forces of the load-bearing structure.